Determinants of Variations in Fecal Neopterin in Free-Ranging Mandrills - Dibakou, Serge Ely; Basset, Didier; Souza, Alain; Charpentier, Marie; Huchard, Elise (Frontiers in Ecology and Evolution, 2019)
Recent progress in designing non-invasive tools to monitor wildlife health offers promising perspectives in immune ecology. In this study, we investigated individual differences in fecal neopterin, a non-invasive marker closely associated with the activation of the cellular immune response, the biological and clinical relevance of which remains to be established. Specifically, we investigated the influence of gut parasites, injuries, environmental and reproductive seasonality, and some individual traits (sex, age, social rank, reproductive state) on fecal neopterin in a natural population of mandrills (Mandrillus sphinx) in Southern Gabon. In this 46-month study, we analyzed neopterin levels from 372 fecal samples collected from 67 individuals of all sexes and ages, running separate models in three categories of individuals that may elicit different strategies of immune investment: (i) across individuals of all sexes and ages, (ii) in adult females, and (iii) in adult males. An increasing proportion of cycling females in the group, reflecting the mating season, positively influenced the concentrations of fecal neopterin across non-adult individuals. The origin of this effect remains unclear as it was unrelated to other ecological (rainfall) or social (rates of male-male aggression) seasonal variables. We did not detect any effects of injuries, parasitism or any other individual traits in these three categories of individuals. Fecal neopterin might be a useful immune marker in some clinical contexts, but our results raise questions regarding its relevance to reveal individual differences in the immune system of a healthy primate population.